EFEKTIVITAS DANA DESA TAHUN 2017-2021 DALAM PEMBANGUNAN EKONOMI DAN INFRASTRUKTUR DI DESA TOTOPO KECAMATAN BILATO KABUPATEN GORONTALO - Ongi, Yusmaya; Paramata, Sri Hantuti; Baderan, Umar Sako; Machmud, Joice (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to determine the extent of the Effectiveness of Village Funds in 2017-2021 in Economic and Infrastructure Development in Totopo Village, Bilato District, Gorontalo Regency. The research method used is research with a quantitative approach and descriptive type. The results of the study are: The allocation of funds for infrastructure has decreased drastically from IDR 717,120,800 in 2017 to IDR 165,776,000 in 2021. This shows a decrease in the priority or scope of infrastructure development in the last five years. The results of the study found that the main problem lies in the lack of technical supervision, the quality of work that does not meet specifications due to the lack of implementer skills, and low transparency in project implementation. This resulted in infrastructure development not being in accordance with the initial plan. Furthermore, funds for economic development are very volatile, with the highest allocation in 2018 of IDR 425,904,900, but decreased to IDR. 214,267,400 in 2021. This fluctuation indicates inconsistent planning, which hinders the success of the program. The results of the study show that aid planning has not been designed in a targeted manner, so that aid is not always on target. In addition, the monitoring system carried out by the Village Consultative Body (BPD) and the village government is less than optimal, and monitoring of the impact of aid has not been carried out in a structured manner